Ecolinguistic Spirits in the Language Environment of the Republic of Armenia - Adilkhanyan , Anahit; Aghajanyan, Zarik (Bulletin of Yerevan University B: Philology, 2025)
In the article, we have used the international achievements of ecolinguistics (also linguistic futurology) and have tried to comprehensively and in accordance with international standards present the language environments of the Republic of Armenia and the Diaspora as a component of the human - nature - language ecosystem․ We aimed to present the peculiarities and “concerns” of the Armenian language to the civilized world in the context of “problems of the Armenian language or Armenianness?”․ During the writing of the article, as a starting point, we chose problematic linguistic realities with functional difficulties, analyzed the external and internal factors negatively affecting the national environment, the process of culturalization of speech, political and social dangerous layers, and recorded eco-end results. As a result of our study, we came to the conclusion that the functional scope of Armenian in the language environment of the Republic of Armenia has expanded, and today the degree of purity and preservation of Armenian is determined by the “eco” complex. The final motto is that one of the main tools for regulating the relations of the Republic of Armenia with the outside world and numerous countries with Armenian communities is the linguistic-cultural component.
Keywords: man-nature-language ecosystem; RA linguistic environment; ecolinguistic thinking; ecospeech; multilingualism; intercultural dialogue; sociolinguistics; critical discourse; ecolinguistic concerns; language variables